Initial teachers training connected with teaching demands in contemporaneity: thematizing the context of a particular institution (Research, Society and Development, 2020)
This study aims to analyze how teachers who work in initial teacher training develop the formative process contributing to new teachers training who are, preferably, connected with teaching demands in contemporary times. For this, a descriptive qualitative research was developed, in which ten professors who work in a Degree course participated. When performing the data analysis, five themes were highlighted, namely: teaching professional trajectory influence; professional training profile; didactic-pedagogical intentionalities, or teachers focus and direction to teaching; reflections seeking growth and professional improvement; and, the conception of what makes a good teacher to act in the initial training of future teachers. We conclude that a qualified training movement is articulated with dialogic and plural learning interactions development, a perspective which requires a willingness to learn to be a teacher and requires a constant reflection process, both for teachers working in initial training, as well as academics training. In this reflexive movement between teachers and future teachers, it is possible to develop a formative process based on teaching demands in contemporary times.